Integrating Generative AI in Inclusive Education: Faculty Perceptions of ChatGPT's Role for Students with Learning Disabilities - Alqarni, Turki Mahdi (European Journal of Social Science Education and Research, 2026)
The rapid expansion of generative artificial intelligence (AI) in higher education has created new opportunities for inclusive teaching, particularly for students with learning disabilities who require adaptive instructional support and accessible learning resources. As a generative AI tool, ChatGPT has gained attention for its capacity to provide interactive explanations, scaffold academic tasks, and personalize responses. This study examines faculty perceptions, perceived challenges, and accessibility concerns regarding the use of ChatGPT in supporting students with learning disabilities within Saudi higher education. Using a descriptive survey design, data were collected from 412 faculty members through a structured questionnaire. Descriptive statistics and two-way analysis of variance were applied according to academic rank and years of experience. Faculty recognized ChatGPT’s usefulness for information access, writing support, and content drafting (M = 3.60, SD = 0.44), while expressing concerns regarding institutional support, accessibility barriers, training needs, and ethical issues (M = 3.68, SD = 0.39). No statistically significant differences were found by academic rank or experience. The findings highlight the need for stronger institutional readiness to support responsible generative AI integration in inclusive higher education.
Keywords: generative AI, learning disabilities, higher education, inclusive education, faculty perceptions.